Influence of Operational Parameters on the Photocatalytic Activity of Powdered TiO2 for the Reduction of CO2 - Oman Zuas; Jin Seog Kim; Jarnuzi Gunlazuardi (Indonesian Journal of Chemistry, 2014)
In this report, the results from a study on the influence of operational parameters on TiO2 photocatalytic activity for CO2 reduction under an ultraviolet-visible (UV-vis) illumination are presented. The results indicated that the TiO2 was found to be active for CO2 reduction with CH3OH as the major products, while other minor products (CO, CH4, and C2H4) were also detected. In addition, the formation of such reduction products was obviously influenced by the operational parameters. Under this study, the optimum operational parameters for CO2 reduction at 298 °K were determined to be: NaOH concentration 0.2 M, TiO2 dosage 2 g/L, volume of the reaction media 75 mL, the pressure of system 800 kPa. It was also found that the increase in UV-vis illumination time have increased the yield of product formation. A possible reaction pathway for the formation of the reduction products is also discussed.